PATH-64. PROSPECTIVE, BLINDED PLASMA BASED ANALYSIS FOR DIAGNOSIS OF NEWLY DIAGNOSED GLIOMA. (11th November 2019) - Lee, Ian; Scarpace, Lisa; Hunt, Rachel; Nelson, Kevin; Patil, Darshana; Datta, Vineet; Akolkar, Dadasaheb; Apurva, Sachin; Fulmali, Pooja; Puranik, Sneha; Snyder, James; Noushmehr, Houtan; et al.
Abstract: INTRODUCTION: In patients with newly diagnosed intracerebral lesions, gliomas are often suspected. However, other conditions such as multiple sclerosis, abscess or lymphoma are possible, as well. Furthermore, biopsy can be challenging due to eloquent and/or deep location within the brain. In this prospective, blinded study, analysis of plasma isolated cell-free DNA and exosome mRNA and miRNA from newly diagnosed glioma patients and from cancer-free volunteers was used to predict disease. METHODS: Plasma was drawn from 52 patients with newly diagnosed gliomas (28 high grade glioma (HGG), 10 low grade (LGG)) and 14 patients without documented history of cancer and recent MRI brain which was negative for brain tumor. High quality DNA and RNA was isolated and sequenced using Next Generation Sequencing and Digital Droplet PCR was used for detection and verification of trace molecular artifacts. Multianalyte processing yielded data that was harmonized and interpreted through an Artificial Intelligence based algorithm to assess for possible glioma and to assign grade in a blinded fashion. EGFRvIII, TP53 and IDH1 mutations were also analyzed and compared to molecular testing from tumor specimens. RESULTS: 66% (25 of 38) of glioma patients were correctly diagnosed as having a malignancy. 43% of HGG and 60% of LGG patients were correctly graded. Of the 14 normal controls, 6 were concluded to be cancer-free. IDH1, EGFRvIII, and TP53 mutation had concordance of 64% (21/33), 82% (14/17) and 36% (5/14), respectively. CONCLUSIONS: Analysis of plasma cell free tumor derived DNA and RNA was relatively sensitive for detecting glioma in treatment naïve patients. In contrast, this analysis was not specific in ruling out malignancy in the normal control patients. Given this profile, in patients with newly diagnosed intracerebral lesions suspicious for glioma, this may be a useful screening test to determine the need for more invasive testing, i.e. biopsy/resection.